Optimalisasi Obyek Wisata Danau Limboto Dalam Rangka Meningkatkan Pendapatan Asli Daerah (PAD) Kabupaten Gorontalo - Sri Sunarti (Program Studi S1 Pariwisata, Universitas Muhammadiyah Gorontalo, 2018)
The development of natural tourism spot. For axample Lake limboto, is very related to the increasing of productivity of economic development, so that it is always faced the interaction condition of several importances which is involving local government environment aspect, society aspect, and private part in land use system. This research applied qualitative method. The data of this reasearch were primary and secondary data. While the technique of data collection were interview, questioner, documentation and observation. The data analysis was conducted by applying conceptualization induction technique/approach. Based on the research, the development of Lake Limboto tourism spot in increasing the Local Revenues of Gorontalo could be conducted through several ways as follows: first, increasing the promotion in tourism especially Lake Limboto as a the tourism spot through cooperation with several intitutes. Second, building the Tourism Information Center (TIC) in an area which could give an accsess in promoting Lake Limboto torism spot. Third, increasing and developing products of Lake Limboto tourism spot. Fourth, implementing the tourism awarness training to the society who lived around Lake Limboto area. Lake Limboto generally were not giving the contribution maximally in increasing the Local Revenue in Gorontalo District, altthough various potential were supporting this tourism spot as one of assets which influenced the local economic